W Radiu Wolna Europa. Działalność Tadeusza Żenczykowskiego (1955-1972). - Trzeskowska, Karolina Natalia (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2018)
Przedmiotem artykułu jest działalność Tadeusza Żenczykowskiego w Radiu Wolna Europa. Z racji piastowanego przez niego stanowiska był on jednym z najbardziej zwalczanych działaczy monachijskiej rozgłośni. Celem artykułu jest ukazanie sylwetki Żenczykowskiego jako osoby zaangażowanej w walkę w obronie prawdy historycznej oraz przeciwko dygnitarzom komunistycznym. Ważnym aspektem jest pokazanie również stosunków wewnątrz zespołu Radia Wolnej Europy. Słowa kluczowe: Żenczykowski, Radio Wolna Europa, działalność antykomunistyczna, Armia Krajowa, emigracja. This article has a biographical character. It tells about activities of Tadeusz Żenczykowski in Radio Free Europe. After the second world war he engaged in a tireless battle against Communism. He became deputy director of the Polish broadcasting department of Radio Free Europe. For 20 years his broadcasts and political commentaries on the turbulent events taking place in his homeland were a regular feature of Polish life and the subject of widespread discussion. Listeners learnt what their own state radio refused to transmit. As we know Radio Free Europe played a critical role in Cold War era Eastern Europe. Unlike government censored programs they publicized anti-Soviet protests and nationalist movements. In the 1972 Żenczykowski went into retirement. He left Munich to live in London. Key words: Żenczykowski, Radio Free Europe, Anti-communism, Emigration